Evaluation of chemical pesticides for the management of Top Borer (Scirpophaga excerptalis Walker) in sugarcane - Paudel, Kapil; Dangi, Naresh; Aryal, Sunil; Regmi, Rashmi (Journal of Agriculture and Natural Resources, 2021)
An experiment was conducted at research field of National Sugarcane Research Program, Jeetpur, Nepal in 2014 and 2016, to evaluate the efficacy of chemical insecticides against sugarcane top borer (Scirpophaga excerptalis Walker). Nine different treatments viz. Chlorantraniliprole 0.4 G, Cartap hydrochloride 4 G, Fipronil 0.3 G, Carbofuran 3 G (standard check) as soil application and foliar spray of Chlorantraniliprole 18.5 SC, Thiodicarp 75 WP, Spinosad 45 SC, Chlorpyrifos 20 EC (standard check) and one untreated check (control) were used in randomized complete block design with three replications. The top borer susceptible genotype, Co 0238 was planted on February and single application of these insecticides was done on July at brood stage against top borers. The lowest 10.65 and 12.43, 13.68, 14.61, 14.15 percentage of top borer damage was found in foliar application of Chlorantraniliprole @ 35g a.i. /ha followed by Spinosad @ 125g a.i. /ha and soil application of Cartap hydrochloride @ 1500g a.i /ha and foliar application of Thiodicarp @ 1500g a.i. /ha and Fipronil @ 100g a.i. /ha. The infestation percentage reduction over control was found highest in Chlorantraniliprole (69.40%) followed by Spinosad (64.29%) treated plots. Furthermore, the cane yield was highest in Chlorantraniliprole (92.30 mt/ha) and Spinosad (90.06 mt/ha) treated plots than that of other insecticide treated plots. The number of millable canes and cane diameter in the plots among the treatment was found non-significant. Based on the infestation reduction rate, foliar application of the chemical insecticide (Chlorantraniliprole 18.5 SC and Spinosad 45 SC) could be better option for chemical management of sugarcane top borer.